1992
DOI: 10.2134/agronj1992.00021962008400050006x
|View full text |Cite
|
Sign up to set email alerts
|

Environment, Cultivar, and Ethephon Rate Interactions in Barley

Abstract: Ethephon[(2‐chloroethyl)phosphonic acid] reduces barley (Hordeum vulgare L.) plant height and lodging potential, but variable effects on yield components and yield also have been reported, depending on ethephon rate, cultivar, and environment. This study was conducted to investigate environment– and cultivar–by‐ethephon‐rate interactions for barley grown under Manitoba conditions. ‘Argyle’, ‘Bedford’, and ‘Samson’ barley were sown on each of two dates in 1986 and 1987, and on single dates in 1988 and 1989, at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
4
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
5
4
0
Order By: Relevance
“…There are reports of reduced grain number following PGR applications, mainly of ethephon at flag leaf stage. This supports the reports of increased abortion of spikelets and grains , Gendy and Höfner 1989, Ma and Smith 1992b, Stobbe et al 1992. Not only do PGR applications at the flag leaf stage have potential to cause yield reductions: CCC applied at the beginning of stem elongation reduced grain yield in wheat.…”
Section: Stress Following Pgr Treatments -Sensitivity Of the Species supporting
confidence: 84%
See 1 more Smart Citation
“…There are reports of reduced grain number following PGR applications, mainly of ethephon at flag leaf stage. This supports the reports of increased abortion of spikelets and grains , Gendy and Höfner 1989, Ma and Smith 1992b, Stobbe et al 1992. Not only do PGR applications at the flag leaf stage have potential to cause yield reductions: CCC applied at the beginning of stem elongation reduced grain yield in wheat.…”
Section: Stress Following Pgr Treatments -Sensitivity Of the Species supporting
confidence: 84%
“…PGRs may in some cases reduce the stress effects. Despite lack of direct evidence of PGR induced stress and some evidence suggesting stress protecting capacity, PGR applications may cause considerable yield reduction, especially when there is no lodging , Cox and Otis 1989, Leitch and Hayes 1990, Taylor et al 1991, Ma and Smith 1992b, Stobbe et al 1992, Bergner and Teichmann 1993, PeltonenSainio and Rajala 2001, Rajala and PeltonenSainio 2002. Reasons for yield reduction could be the timing of applications and interaction between PGR and cultivar.…”
Section: Stress Following Pgr Treatments -Sensitivity Of the Species mentioning
confidence: 99%
“…In every case ‘Doyce’ plant height was significantly reduced, from an average of 32.7 inches when ethephon was not applied to 23.0 inches with the 2.5 oz a.i./acre ethephon rate. Further decreases in height were not observed with rates above 2.5 oz a.i./acre which agrees with the findings of Stobbe et al (17). Similar to ‘Doyce,’ VA00H‐65 height was significantly reduced when ethephon was applied, but there was no difference among rates.…”
Section: Plant Heightsupporting
confidence: 92%
“…When ethephon was applied at the boot stage, yield of the cultivar ‘Leger’ was increased by 24% while yield of ‘Argyle’ decreased 19%. A significant interaction between ethephon rate and cultivar for grain yield was also reported by Ma and Smith (9) and Stobbe et al (17).…”
Section: Plant Growth Regulator Effects On Barleysupporting
confidence: 77%
“…Reported optimal growth stages for ethephon application to barley are contradictory. This may be due to testing at only a few phenological stages (Dahnous et al, 1982;Ma and Smith, 1992a) or to environmental conditions immediately following ethephon treatment (Simmons et al, 1988;Ma et al, 1992;Ma and Smith, 1992a;Stobbe et al, 1992). The optimal growth stage for ethephon application to barley was determined to be the flag leaf stage (Stevens and Palmer, 1983;Berengier et al, 1983;Easson, 1983), the early boot stage (Duke and Rutger, 1970), or the late boot stage (Dahnous et al, 1982), while others found that growth stage was relatively unimportant (Hill et al, 1982).…”
mentioning
confidence: 99%